Association between vitamin D receptor polymorphisms and acute pancreatitis: A protocol for systematic review and meta analysis. Issue 16 (23rd April 2021) - Li, Xiaofeng; Gan, Xianghai; Gong, Junzuo; Mou, Tianyi; Zhou, Hua; Li, Mengqin
Abstract: Background: Several studies have been performed to investigate the association between vitamin D receptor ( VDR ) gene polymorphism and acute pancreatitis, but the results are inconclusive. We conducted this meta-analysis for a precise estimation of the association between BsmI (rs1544410), ApaI (rs7975232), TaqI (rs731236), and FokI (rs2228570) polymorphisms and acute pancreatitis. Methods: Appropriate studies were retrieved by searching Web of Science, PubMed, Scopus, and Google scholar databases, until January 31, 2021. Two reviewers independently conducted data extraction and literature quality evaluation. Odds ratios and 95% confidence intervals were calculated to evaluate the strength of the association. All of the data were analyzed with Stata 16.0. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusions: This meta-analysis will summarize the association between BsmI, ApaI, TaqI, and FokI polymorphisms and the risk of acute pancreatitis. Ethics and dissemination: Ethical approval was not required for this study. The systematic review will be published in a peer-reviewed journal, presented at conferences, and shared on social media platforms. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/83W7R.